Hubungan Durasi Tindakan Operasi Dengan Kejadian Carpal Tunnel Syndrome Pada Perawat Instalasi Bedah Sentral Di Rsud Kajen Dan Rsud Kesesi Kabupaten Pekalongan - Pipit Nurainun; Wahyuningsih Wahyuningsih; Dyah Restuning P (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to examine the relationship between operative duration and the incidence of Carpal Tunnel Syndrome (CTS) among nurses working in the Central Operating Room of Kajen and Kesesi Regional Hospitals, Pekalongan Regency. A quantitative empirical approach with a correlational design was applied, involving 51 nurses selected through total sampling. Data were collected using structured observation to measure operative duration in monthly hours and the validated Quick Disabilities of the Arm, Shoulder, and Hand (Quick DASH) questionnaire to assess CTS-related functional impairment. Statistical analysis using Spearman Rank test revealed a significant and strong positive relationship between operative duration and CTS incidence. These findings indicate that prolonged exposure to operative activities increases biomechanical stress on the median nerve, leading to functional impairment. The study highlights the importance of ergonomic interventions, workload management, and early detection strategies in preventing CTS among operating room nurses. This research contributes to occupational nursing science by providing empirical evidence and proposing a context-based preventive model relevant to hospital settings.